Randomized factorial trial of high-dose intravenous streptokinase, of oral aspirin and of intravenous heparin in acute myocardial infarction. ISIS (International Studies of Infarct Survival) pilot study. - Collins, R (1987)
619 patients with suspected acute myocardial infarction (MI) were randomized to receive either a high-dose short-term intravenous infusion of streptokinase (1.5 MU over one hour) or placebo. Using a '2 X 2 X 2 factorial' design, patients were also randomized to receive either oral aspirin (325 mg on alternate days for 28 days) or placebo, and separately randomized to receive either intravenous heparin (1000 IU h-1 for 48 hours) or no heparin. Streptokinase (SK) was associated with a nonsignificant (NS) increase in non-fatal reinfarction (3.9% SK vs 2.9% placebo) and decrease in mortality (7.5% vs 9.7% in hospital plus 6.1% vs 8.7% after discharge). After SK, there were significantly fewer strokes (0.5% vs 2.4%; 2P less than 0.05), but significantly more minor adverse events (e.g. hypotension and bradycardia, allergies, bruises or minor bleeds, nausea). Aspirin was associated with fewer non-fatal reinfarctions (3.2% aspirin vs 3.9% placebo; NS), deaths (in hospital: 6.1% vs 10.5%; 2P less than 0.05, and after discharge: 7.0% vs 6.9%; NS), and strokes (0.3% vs 2.0%; NS). Heparin was associated with a decrease in reinfarction (2.2% heparin vs 4.9% no heparin; NS), though not in mortality (in hospital: 8.0% vs 8.5%; NS, and after discharge: 7.0% vs 6.9%; NS), and with a trend towards more strokes (1.6% vs 0.7%; NS) and more bruising and bleeding (14% vs 12%; NS). To assess more reliably the effects of aspirin and of this SK regimen on mortality, about 400 hospitals worldwide are now collaborating in a large (about 20,000 patients planned) randomized trial (ISIS-2), for which the present study was a pilot.